Genetic Interactions Between the Meiosis-Specific Cohesin Components, STAG3, REC8, and RAD21L - Ward, Ayobami (G3 (Bethesda), 2016)
Cohesin is an essential structural component of chromosomes that ensures accurate chromosome segregation during mitosis and meiosis. Previous studies have shown that there are cohesin complexes specific to meiosis, required to mediate homologous chromosome pairing, synapsis, recombination, and segregation. Meiosis-specific cohesin complexes consist of two structural maintenance of chromosomes proteins (SMC1α/SMC1β and SMC3), an α-kleisin protein (RAD21, RAD21L, or REC8), and a stromal antigen protein (STAG1, 2, or 3). STAG3 is exclusively expressed during meiosis, and is the predominant STAG protein component of cohesin complexes in primary spermatocytes from mouse, interacting directly with each α-kleisin subunit. REC8 and RAD21L are also meiosis-specific cohesin components. Stag3 mutant spermatocytes arrest in early prophase (“zygotene-like” stage), displaying failed homolog synapsis and persistent DNA damage, as a result of unstable loading of cohesin onto the chromosome axes. Interestingly, Rec8, Rad21L double mutants resulted in an earlier “leptotene-like” arrest, accompanied by complete absence of STAG3 loading. To assess genetic interactions between STAG3 and α-kleisin subunits RAD21L and REC8, our lab generated Stag3, Rad21L, and Stag3, Rec8 double knockout mice, and compared them to the Rec8, Rad21L double mutant. These double mutants are phenotypically distinct from one another, and more severe than each single knockout mutant with regards to chromosome axis formation, cohesin loading, and sister chromatid cohesion. The Stag3, Rad21L, and Stag3, Rec8 double mutants both progress further into prophase I than the Rec8, Rad21L double mutant. Our genetic analysis demonstrates that cohesins containing STAG3 and REC8 are the main complex required for centromeric cohesion, and RAD21L cohesins are required for normal clustering of pericentromeric heterochromatin. Furthermore, the STAG3/REC8 and STAG3/RAD21L cohesins are the primary cohesins required for axis formation.